Future Skylight - Karlsson,Felix; Gustafsson,Robin (2014)
The working environment on top of an 80 - 120 meters high horizontal-axis wind turbine isn’t like an average working environment. The high wind speeds, the slippery rain, the limited mobility and the pure height makes it a very dangerous and difficult place to work at. To make sure the service team can feel safe and at ease while working outside on the top of a wind turbine, all the equipment used needs to be specifically customized for its special use and environment at the wind turbine. Today's skylights, openable hatches, aren’t designed especially for usage at wind turbines and that makes them lack in necessary strength, safety and usability. This Master’s thesis aims to solve the problems with the current skylights at horizontal-axis wind turbines that connects the inside of the nacelle to the roof outside. The goal is to make the perfect skylight for wind turbines that is safer, cheaper, stronger and better in usability aspects. This report describes the process from a list of requirements, through research, concept generation, concept selection and testing to a finished prototype ready to be manufactured and subjected to final testing.
Keywords: skylight; wind; turbine; safety; usability; technical design